Efficacy and safety of camrelizumab in combination with neoadjuvant chemotherapy for ESCC and its impact on esophagectomy - Qiao, Yujin; Zhao, Cong; Li, Xiangnan; Zhao, Jia; Huang, Qi; Ding, Zheng; Zhang, Yan; Jiao, Jia; Zhang, Guoqing; Zhao, Song (Frontiers in Immunology, 2022)
Background: Esophageal squamous cell carcinoma (ESCC) is the most common type of esophageal cancer in China. The use of neoadjuvant immunotherapy for the treatment of ESCC is gradually increasing. Camrelizumab is one such immune checkpoint inhibitor (ICI) used for treatment. In this retrospective study, we explored the efficacy, safety, and short-term perioperative prognosis of camrelizumab in combination with neoadjuvant chemotherapy for ESCC. Materials and Methods: A total of 254 Chinese patients with ESCC were enrolled in the study; 48 received camrelizumab in combination with neoadjuvant chemotherapy (C-NC group), and 206 received neoadjuvant chemotherapy (NC group). All patients underwent surgery after the completion of 2 cycles of neoadjuvant therapy. Results: Twenty patients (20/48, 41.7%) in the C-NC group and 22 patients (22/206, 10.7%) in the NC group achieved a pathologic complete response (pCR) (p<0.001). Twenty-nine patients (29/48, 60.4%) in the C-NC group and 56 patients (56/206, 27.2%) in the NC group achieved major pathologic remission (MPR) (p<0.001). There was a lower incidence of myelosuppression during neoadjuvant therapy in patients in the C-NC group (33/48, 68.8%) than in the NC group (174/206, 84.5%, p=0.012). The total incidence of adverse reactions during neoadjuvant therapy was also lower in the C-NC group (37/48, 77.1%) than in the NC group (189/206, 91.7%, p=0.003). Patients in the C-NC group had more lymph nodes cleared during surgery than those in the NC group (34 vs.30, p<0.001). The logistic model showed that the treatment regimen, age, and presence of lymph node metastasis were influential factors for achieving a pCR in these patients (p<0.001). Regarding other adverse events and surgery-related data, there were no significant differences observed between the two groups. Conclusion: Camrelizumab in combination with neoadjuvant chemotherapy is an efficacious neoadjuvant regimen with an acceptable safety profile and does not increase the difficulty of surgery or the incidence of complications. A pCR is more likely to be achieved in patients treated with camrelizumab in combination with neoadjuvant chemotherapy, in younger patients, or in those without lymph node metastases.